PERLINDUNGAN HUKUM BAGI PIHAK PEMBELI DALAM HAL TERJADI PERBUATAN MELAWAN HUKUM TERKAIT SENGKETA JUAL BELI TANAH (STUDI PUTUSAN NOMOR : 121/PDT.G/2017/PN.BDG.) - Inten Rosita; Endang Pandamdari (Jurnal Hukum Adigama, 2019)
Tort is every thing that causes detriment to other people, requires the guilty one who causes detriment to pay compensation. Tort recognizes two concepts of compensation, those are material compensation and immaterial compensation.  The civil code manage the immaterial compensation which can only be given in particular things, such as the matter of death, seriously injured, and humiliation. In the decision of the Bandung district court number :121/PDT.G/2017/PN.BDG. the case of the act tort  which relates to the land sale and purchase dispute, the judges granted the immaterial and moral compensation in the amount of two billion rupiah. Due to Hanny Untar proved for doing tort that she has pressured the Notary Euis Komala, S.H. to make a statement.The author use normative legal research and uses interview data as supporting data. The research reveal that the decision of the Bandung District Court number : 121/PDT.G/2017/PN.BDG. About the immaterial and moral compensation which caused by tort, because of doing defamation with inaccurate police report. Due to the judges consideration, the police report is not a form af tort, that everyone has the right to make a police report which is protected by law.